PENGARUH KONTEN TIKTOK @REXI TERHADAP MINAT FOLLOWERS UNTUK MODIFIKASI MOTOR - Lumban Gaol, Richard Kurnadi; Abidin, Sholihul (LPPM Universitas Putera Batam, 2024)
One social media platform that is currently quite familiar to Indonesian society is TikTok. TikTok is a social networking platform used to create content in the form of short videos. Someone may become famous on TikTok because of their interesting content; these people are called